2019
DOI: 10.4028/www.scientific.net/jnanor.56.28
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Fe:TiO<sub>2</sub> Particles

Abstract: TiO2 and iron-doped TiO2 were synthesized by sol-gel method. TiO2 and 0.5 %mol Fe:TiO2 were calcined at 500 and 800 °C for 3 h. The synthesized particles were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), UV-VIS diffuse reflectance spectrophotometry (UV/DRS), scanning electron microscopy (SEM) and scanning electron microscope-energy dispersive X-Ray analysis (SEM-EDX). The XRD patterns of all samples that were calcined at 500 °C showed only anatase phase. On increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…01-075-8897. Signal from the 0.125% Fe-TiO2 crystalline phase containing Fe of the doping elements could not be observed, which consistence with several articles [26,27]. However, a increase in the anatase peak intensity was observed for Fe-doped TiO2, in comparison with TiO2.…”
Section: ( ) (mentioning
confidence: 79%
See 2 more Smart Citations
“…01-075-8897. Signal from the 0.125% Fe-TiO2 crystalline phase containing Fe of the doping elements could not be observed, which consistence with several articles [26,27]. However, a increase in the anatase peak intensity was observed for Fe-doped TiO2, in comparison with TiO2.…”
Section: ( ) (mentioning
confidence: 79%
“…The Fe-doped TiO2 amorphous is then calcined at 450 °C to form the crystal structure of Fe-doped TiO2 [21]. During calcination process, both of the Ti 4+ and Fe 3+ cations compete with O atoms to form Fe−O−Ti bonding in the TiO2 lattice and crystallite growth occurs simultaneously [3,21,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible explanations for this phenomenon. One of the most recurrent and established claims that the insertion of iron, which is a conductive metal, produces intermediate energy levels between the valence band and conduction band, compared to samples without it [16]. Then the material is able to absorb a larger part of the solar spectrum as it requires less energy photons to promote the electrons from their valence band to the conduction band.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…As compared to anatase-and rutile-TiO 2 nanoparticles, the rutile-TiO 2 evidenced an enhancement in the antibacterial activities using Escherichia coli, Bacillus subtilis, and Staphylococcus aureus. 18 Ochoa Rodri ́guez et al reported the sol−gel preparation of mesoporous Fe-TiO 2 nanoparticles by varying the concentration of iron. As compared to Fe-TiO 2 samples prepared by using 0.0125, 0.025, 0.1, and 1.0 wt % concentrations, the sample based on the 0.1 wt % concentration showed an improvement in the photocatalytic activity, which was assigned to the reduced optical band gap.…”
Section: Introductionmentioning
confidence: 99%